Sir Cumference and the First Round Table : A Math Adventure - Cindy Neuschwander (Watertown, United States Charlesbridge Publishing,U.S., 1999)
King Arthur was a good ruler, but in this math adventure he needs a good ruler. Geometry is explained with humor in SIR CUMFERENCE AND THE FIRST ROUND TABLE, making it fun and accessible for beginners. What would you do if the neighboring kingdom were threatening war? Naturally, you'd call your strongest and bravest knights together to come up with a solution. But when your conference table causes more problems than the threat of your enemy, you need expert help. Enter Sir Cumference, his wife Lady Di of Ameter, and their son Radius. With the help of the carpenter, Geo of Metry, this sharp-minded team designs the perfect table conducive to discussing the perfect peace plan. Thanks to Sir Cumference, even the most hesitant will be romancing math.